Efficiency Analysis of PT Dayamitra Telekomunikasi Tbk in the Telecommunication Infrastructure Industry Using the Data Envelopment Analysis (DEA) Method - Kaila Zahra Nandika; Budi Sulistyo; M. Almaududi Pulungan (Jurnal Indonesia Sosial Teknologi, 2024)
The projected increase in the number of telecommunication towers in Indonesia by 100% by 2026 reflects the rapid growth in the telecommunications infrastructure sector, driven by increasing data demand and the adoption of 5G technology (WCA, 2021). In the Asia-Pacific region, similar demand indicates a huge opportunity for the expansion of this industry. PT Dayamitra Telekomunikasi Tbk (Mitratel) is one of the companies that excels in the Telecommunication infrastructure industry in Indonesia. This study uses the Data Envelopment Analysis (DEA) method, which is effective in measuring the efficiency of organizational units in various fields. The results show that in five years of observation, Mitratel managed to achieve full efficiency in almost all years of observation, with high efficiency level results comparable to PT Sarana Menara Nusantara Tbk. Meanwhile, the annual efficiency level for Indus Towers and China Tower is quite volatile, although it remains at a high value. Trend analysis and Pearson Correlation coefficient between average efficiency and input/output variables show that the current assets, non-current liabilities, and CAPEX variables have a significant influence on Mitratel's efficiency with a negative correlation, while the current liabilities variable has a significant influence with a positive correlation.